2017
DOI: 10.1002/ppul.23783
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in childhood wheezing characteristics: A whole population study

Abstract: Knowledge of these age-related changes in wheezing illness is informative for health care planning and the design of future research projects and questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Our finding that 28% of the 12‐year‐old asthmatics only had asthma with a cold is notable and was higher than we expected. However, the percentage was in line with British findings . In a large population‐based cohort of children from Leicestershire, UK, Jurca et al found that the relative prevalence of episodic viral wheeze in the children aged 10–13 was 40%.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our finding that 28% of the 12‐year‐old asthmatics only had asthma with a cold is notable and was higher than we expected. However, the percentage was in line with British findings . In a large population‐based cohort of children from Leicestershire, UK, Jurca et al found that the relative prevalence of episodic viral wheeze in the children aged 10–13 was 40%.…”
Section: Discussionsupporting
confidence: 75%
“…However, the percentage was in line with British findings . In a large population‐based cohort of children from Leicestershire, UK, Jurca et al found that the relative prevalence of episodic viral wheeze in the children aged 10–13 was 40%. That means that four in 10 children with wheeze only wheezed during respiratory infections.…”
Section: Discussionsupporting
confidence: 75%
“…Acute wheezing with bronchoconstriction is most common before school age compared to any other age group . Furthermore, acute exacerbations of asthma account for approximately 10% of emergency visits in children and result in hospitalization of 20% to 40% of cases .…”
Section: Introductionmentioning
confidence: 99%
“…In children, the prevalence of current wheezing varies significantly by geography and may be as high as 30% while the prevalence of reported “wheeze ever” may reach close to 50% . A recent study of a large population‐based cohort of children ( n = 7670) found “current wheeze” most commonly reported in 1‐year‐olds (36%), decreasing to 17% in adolescents at 14‐17 years of age …”
Section: Introductionmentioning
confidence: 99%